Melatonin regulates proliferation, apoptosis and invasion of trophoblasts in preeclampsia by inhibiting endoplasmic reticulum stress. (27th June 2022) - Zhou, Chufan; Ding, Yiling; Yu, Ling; Nie, Yanting; Yang, Mengyuan
Abstract: Aims: Clinical evidence indicated the activation of endoplasmic reticulum stress (ERS) in pregnant women with preeclampsia (PE), and the regulatory role of melatonin (MT) in ERS. This study aims to explore the possible effect and mechanism of MT on ERS and on the infiltration of trophoblasts in PE. Methods: The serum expression levels of MT and GRP78 in pregnant women with PE were measured. The cell proliferation, invasion, migration and apoptosis of trophoblasts were also determined. The trophoblast cell infiltration in placenta tissues was detected in EVOS image system. The expressions of ERS related proteins were measured by RT‐qPCR and western blot. Key results: The PE‐serum treatment on HTR‐8/SVneo cells led to activated ERS and suppressed cell biological functions. PE mouse models after MT treatment or 4‐PBA treatment had reduced blood pressure, proteinuria, apoptosis and increased foetus and placenta weight, in addition to enhanced cell infiltration. Conclusions: In vivo and in vitro evidence demonstrated MT can simultaneously suppress ERS and ASK1/JNK signal pathway in PE to promote the infiltration of trophoblasts.